Study of removal process of manganese using synthetic calcium hydroxyapatite from an aqueous solution. Issue 14 (21st March 2016) - Gogoi, Diganta; Shanmugamani, A.G.; Rao, S.V.S.; Kumar, T.; Velmurugan, S.
Abstract: Calcium hydroxyapatite (HAP) was synthesized by a precipitation method, and it was characterized by the XRD technique. The removal of manganese(II) from an aqueous solution on HAP as a function of contact time, pH, ionic strength, temperature, and other monovalent and bivalent ions was studied using a radiotracer, 54 Mn, in the batch process. The sorption of manganese on HAP was pH independent ranging from 4 to 6 due to the buffering properties of HAP. The sorption of manganese was rapid, and the percentage of manganese sorption was 99% during the first 20–30 min of the contact time, when the initial concentration of manganese ions was 1 mg/L (ppm) at pH of 5. The sorption kinetics showed that the sorption of manganese on HAP could be simulated by the pseudo-second-order kinetic model very well. The maximum sorption capacity of HAP for manganese calculated based on the Langmuir model was 58.99 mg/g at pH 5.1 and T = 300 K. The thermodynamic parameters from the temperature-dependent sorption isotherms indicated that the manganese sorption on HAP was an endothermic and spontaneous process. It was observed that in the presence of bivalent ions like Co 2+, the manganese sorption by HAP decreases, whereas it remains same in the presence of monovalent ions like Na + .